Artificial membranes as models in penetration investigations. Issue 1 (12th June 2012) - Krulikowska, M.; Arct, J.; Lucova, M.; Cetner, B.; Majewski, S.
<x xml:space="preserve">Abstract</x> Background/aims In vitro methods used in the research of transepidermal transport of active substances generally rely on the penetration rate of test compounds through standard membranes. Models typically used in penetration experiments are specially prepared human or animal skin samples or synthetic membranes. The objective of this study was to establish if the test results for an artificial liposome membrane can be extrapolated to determine the actual bioavailability of active substances. Methods Tests were conducted in a side‐by‐side diffusion cell. As model membranes, a liquid‐crystal lipid membrane (LM), phospholipid membrane (PM) and pig skin sample were used. The test compounds were eight synthetic dyes used in hair colouring products. Results/Conclusion Research findings reveal that membranes composed of lipids, identical to those present in the epidermis and forming analogical liquid‐crystal structures provide a close approximation of the actual bioavailability of active substances (correlation between the results obtained for pig skin and LM was significant: R = 0.95 and R = 0.93 in the presence of a 1% Sodium dodecyl sulphate in donor system). Unlike biological membranes, intercellular cement does not contain phospholipids. The observed correlation between penetration coefficients through the PM and pig skin was not significant (R = 0.82). The experiments confirm that the PM constitutes a less credible model for the studies of transepidermal transport in real life conditions.